Promoting participation in value chains for pulses in Malawi: Who and where to target - Benson, Todd (International Food Policy Research Institute, 2020)
In this Policy Note, we examine both household and spatial factors that may drive participation by smallholder farming households in commercial value chains for pulses, legume crops that are primarily harvested for their dry seed. Here the focus is on value chains for common bean (Phaseolus vulgaris), cowpea (Vigna unguiculata), and pigeonpea (Cajanus cajan). Bean and pigeonpea are particularly important secondary crops within many smallholder farming systems in Malawi, while cowpea is less common. All are commonly grown as intercrops in smallholder farming systems, primarily with maize.